An improved method for radium-isotopes quartet determination by alpha-particle spectrometry by using 225Ra (229Th) as isotopic tracer. (January 2019) - Pérez-Moreno, S.M.; Gázquez, M.J.; Casas-Ruiz, M.; San Miguel, E.G.; Bolívar, J.P.
Abstract: A new method for the determination of radium quartet ( 223, 224, 226, 228 Ra) in environmental samples by alpha-particle spectrometry with PIPS detectors is described. This uses 225 Ra as yield tracer, in equilibrium at the beginning with 229 Th. Thorium is removed from the sample by using AG1X8 anion-resin, and then radium isotopes are isolated and purified with a cation-exchange column Biorad AG50X8, verifying that Ac has been fully removed from the sample to ensure the good evaluation of the Ra yield (average decontamination factor > 92%). Finally, the counting source of radium is obtained by micro-precipitation with BaSO4 . This method produces high spectral resolution (<35 keV), and quantitative Ra recoveries (>70%). In this new method, NH4 Ac in 0.1 M HNO3 is used to remove the 225 Ac contained in the sample in order to avoid its future spectral interference in the yield calculation. The method has been validated by using certified reference samples with known concentrations of radium isotopes. Highlights: A new simplest method for radium quartet measurement was evaluated. 225 Ra as isotopic tracer was used. A depth study of 225 Ra- 225 Ac separation was carried out.